Doc Savage : Murder Island - Book 2 - Patterson, James, 1947-; Sitts, Brian (New York : Litte, Brown and Company, 2024)
"When professor turned crime-fighter Brandt 'Doc' Savage and his girlfriend Kira Sunlight land on a desert island in the middle of the Atlantic, they think they've found a perfect utopia. An escape from their tumultuous pasts. But they don't have long to enjoy their newfound peace before they are violently separated and dragged to opposite ends of the Earth. Doc's search for Kira takes him from the coast of Brazil to northern Europe and the jungles of the Congo, and he discovers they are entangled in a global conspiracy that is bigger he ever could have imagined"--
Keywords: Savage, -- Doc (Fictitious character) -- Fiction; College teachers -- Fiction; Thrillers (Fiction)